Dead bodies disposal and record management guidelines and procedures during Covid-19 pandemic in Malaysia: a conceptual study / Wardatul Hayat Adnan, Kholyn Ruran Jonathan and Dazmin Daud - Adnan, Wardatul Hayat; Jonathan, Kholyn Ruran; Daud, Dazmin (Centre For Media And Information Warfare Studies, 2021)
The outbreak of coronavirus disease that emerged in December 2019 (known as the COVID-19 pandemic) has caused distress to many countries worldwide. Malaysia is one of the developing countries that is dealing with and monitoring the transmission of the disease in the same stressful climate. One of the most critical issue during this pandemic is the proper way to handle and manage bodies of COVID-19 victims so as to reduce the risk of spreading the virus from the dead to the living. Since the government is unfamiliar with handling a potentially lethal pandemic, it has taken steps to study and obtain information from China, the region where the virus originated. Data were also collected from other countries. On top of that, other policies and guidelines relating to the management of dangerous diseases were also referred to better manage the pandemic situation in Malaysia. This study looked into the current guidelines and procedures in managing the disposal of dead bodies and its record management for COVID-19 victims in Malaysia. It also looked into recommendations provided by other international agencies. It is hope that this study could be useful for the better management of COVID-19 related deaths and its data records.